Readiness of Parents in Caring for Low Birth Weight Infants Through Low Birth Weight Care Education - Novi Indrayati; Dona Yanuar Agus Santoso (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Low birth weight babies weighing less than 2500 grams have the general condition of being smaller than normal birth weight babies. LBW is a high-risk baby so that it requires special care to anticipate emergency conditions that threaten death, a situation that is different from that of babies in general which can affect parents' readiness to care for babies. The purpose of this study was to see the effect of providing LBW education on parents' readiness to care for LBW. This study used a quasi-experimental design with pre post-test with control. The population of this research is parents who have LBW babies in Kendal area hospitals. The sampling technique used accidental sampling with a total sample of 40 people with LBW infants, the sample was classified into two groups, namely 20 respondents as the intervention group and 20 other respondents as the control group. Data analysis to see the readiness of parents before and after being given education used the Mc Nemar test, while the bivariate analysis in this study used the Chi-Square test to see the effect of providing LBW care education on parental readiness to care for LBW. The results showed that there were differences in readiness to care for LBW before and after being given LBW care education with a value of 0.004 tilapia using the Mc Nemar test, and there was an effect that provided LBW care education on parental readiness to care for LBW with a P-value of 0.002 using the Chi-Square test.